Effect of external pH on acidification and excretion of ethanol intermediates by Candida utilis - Páca, J; Votruba, J (Folia microbiologica, 1991)
External pH affects the acidification induced by ethanol. The apparent specific rate of acidification depends on the dissociation properties and production of carbon dioxide, acetic and lactic acid which are intermediates of ethanol oxidation. The organic acids are transported by Nernst-Einstein diffusion. We designed and identified a new and simple mathematical model that allows us to describe the effect of external pH on nonstationary transport of dissociated intermediates of ethanol oxidation.
Keywords: draslík; Potassium; Lactic Acid; oxidace-redukce; Models, Biological; ethanol; acetáty; aktivní transport; Biological Transport, Active; Kinetics; Carbon Dioxide; laktáty; kyselina octová; Acetic Acid; Hydrogen-Ion Concentration; biologické modely; oxid uhličitý; Oxidation-Reduction; Acetates; Ethanol; koncentrace vodíkových iontů; kyselina mléčná; Lactates; kinetika; Candida